Comparison of the dietary fibre composition of old and modern durum wheat (Triticum turgidum spp. durum) genotypes - De Santis, Michele Andrea (Food Chem, 2018)
It has been suggested that intensive breeding has led to decreased contents of health-promoting components in modern wheats. We therefore compared the contents and compositions of the major dietary fibre components, arabinoxylan and β-glucan, in semolina and wholemeal flour of old and modern Italian durum wheats. No differences in total arabinoxylan content were observed but the modern varieties had higher proportions of soluble arabinoxylan in wholemeals and of β-glucan in semolina. The study therefore provides no evidence that intensive breeding has had negative effects on the contents of dietary fibre components in durum wheat. However, comparison of material grown over two years indicated that the content and composition of arabinoxylan and β-glucan were more stable in the older than in the modern genotypes. The identification of modern cultivars with high viscosity associated with a high content of β-glucan suggests that they are good sources of fibre for human health.